Organizational change, new information and communication technologies and the demand for labor in services - Martin Falk (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
Between 1993 and 1995, the majority of German firms in services introduced new organizational practices (OC), in particular total quality management systems, certified ISO 9000, lean administration, flatter hierarchies, delegation of authority and ICT-enabled organizational changes). This paper analyzes the impact of organizational change as well as the impact of the introduction of information and communication technology (ICT) on actual labor demand as well as on employment expectations. The focus of attention is also directed to potential endogeneity of OC using treatment effect models as well as multivariate probit models. The empirical results suggest that OC has a positive effect on actual employment growth given output and factor price changes. Furthermore, we find that organizational change has a positive impact on expected employment for all skill groups except for unskilled labor. New ICT and the share of training expenditures are primary forces behind OC. Finally, employment effects are robust to endogeneity of organizational change.
Keywords: O33; J23; 330; organizational change; ICT; skill structure; Organisatorischer Wandel; Informationstechnik; Computergestütztes Verfahren; Beschäftigungseffekt; Dienstleistungssektor; Arbeitsnachfrage; Qualifikation; Deutschland